A select inhibitor of MORC2 encapsulated by chimeric membranecoated DNA nanocage target alleviation TNBC progression - Xiaohan Su; Yunbo Luo; Yali Wang; Peng Qu; Jun Liu; Shiqi Han; Cui Ma; Shishan Deng; Qi Liang; Xiaowei Qi; Panke Cheng; Lingmi Hou (Materials Today Bio)
Triple-negative breast cancer (TNBC) is the most malignant type of breast cancer and lacks effective targeted therapeutic drugs, resulting in a high recurrence rate and worse outcome. In this study, bioinformatic analysis and a series of experiments demonstrated that MOCR2 was highly expressed in TNBC and closely associated with poor prognosis, indicating that MOCR2 may be a potential therapeutic target for TNBC. Subsequently, Angoline was identified as an inhibitor of MORC2 protein by high-throughput screening and can significantly kill the TNBC cells by blocking cell cycle and inducing apoptosis. Furthermore, the biomimetic nanodrug delivery system (PMD) was designed by encapsulating tetrahedral DNA nanostructures with biomimetic cell membrane, and it can efficiently evade the phagocytosis of immune system and target TNBC tissue. Additionally, PMD can markedly enhance the killing effect of Angoline on TNBC tumors. Therefore, PMD-enveloped Angoline provide a highly effective targeted therapeutic regimen for TNBC and may improve the outcome for patients with TNBC.